Optimizing Pencak Silat Learning with a Digital Audio Approach - novial azhar, novial azhar; Gustuawati, Resty; Gani, Ruslan Abdul (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
Audio digital Pencak Silat learning maintains traditional Indonesian values ​​and improves physical skills. Students can be more motivated to learn Pencak Silat because this technology allows them to learn in a more interesting and interactive way. It is hoped that this step can improve Pencak Silat learning in elementary schools, encourage a healthy lifestyle, and preserve national culture. This study utilizes quantitative and qualitative descriptive surveys. A total of 65 of them are students, trainers and stakeholders in the field. After the survey was completed, most participants stated that they wanted to use additional media to teach pencak silat. As many as 80% of students, 65% of coaches and all sports education experts say that digital audio can be a great tool to enhance the learning experience. In terms of views on digital audio, 85% of students, 70% of trainers and all education experts stated that in pencak silat learning, 70% of students and 50% of trainers said This shows that although digital audio is not new, there are still opportunities to introduce and teach a wider range of people to use this technology. Learning sports, especially pencak silat, is assisted by digital audio media. The use of digital audio as a medium for learning pencak silat has great potential to answer various challenges, especially in terms of flexibility and attractiveness of learning. This could be applied more widely across schools